(3JGQjN GdUMGaI GdYGdejI (B/s - (3JhOhQha s; (3NVhQ(B,(3CPjHs ((3OeTb (B:s (3COjH NVhQ ,s, 1990)
(3jOQS gPG GdcJGH XghQ h JWhQ GdUMGaI aj GdHdOGf GdZQHjI GdQFjSjI GdCQHY eDcOG Ydi eUehfgG GdSjGSj h WGHYgG GdELJeGYjs
Keywords: (3GdUMGaI GdYGdejIs; (3JGQjN GdUMGaI GdEYdGejIs